Transient temperature change within a wall embedded insulation with variable thermal conductivity - Maatouk Khoukhi; Shaimaa Abdelbaqi; Ahmed Hassan (Case Studies in Thermal Engineering, 2020)
This paper examines the change of the temperature through a typical wall assembly comprising a polystyrene insulation material (EPS) with constant and variable thermal conductivity (λ). Four levels of the insulation density, namely, low density (LD), high density (HD), super high density (SHD), and ultra-high density (UHD) impeded at three different locations within the wall have been considered in this study. During the day, the evolution of temperatures through the wall section was observed on inner wall surface when EPS is located at different positions of the wall section. Thereafter, the thermal performance across the wall section incorporating insulation layers at different positions applying variable λ-value was compared to a non-variable thermal conductivity case by quantifying the net heat reduction due to the λ-relationship with time. As a result obtained, the change of the temperature through the wall with variable λ is higher compared to the case of constant λ. The temperature change on the inner wall surface with constant and variable λ is shown to decrease as the position of the insulation material is located toward the inner wall surface. Therefore, locating the insulation material in the middle of the wall assembly will provide the best dynamic thermal performance.